Analisis Keberlanjutan Usaha Peternakan Sapi Perah Pada Peternak Milenial (Studi Kasus di Milk Collection Point Warnasari, Kecamatan Pangalengan) - Julian, Muhammad Waskita; Alim, Syahirul; Sulistiyawati, Marina (Innovative: Journal Of Social Science Research, 2024)
This sustainability analysis is viewed from 5 dimensions, namely ecological, economic, social, institutional and technological which influence business sustainability. The research was conducted at MCP Warnasari, Pangalengan District in July 2024. The subjects of this research were millennial breeders who are members of KPBS Pangalengan at MCP Warnasari, although the focus of this study was the sustainability of dairy farming businesses among millennial breeders. The method used is a case study by collecting primary data through interviews, observations and questionnaires with millennial breeders (census), then secondary data is also collected from various literature sources and the KPBS Pangalengan data set. Data processing was carried out with the Rapfish (Rapid Appraisal of Fisheries) application. All of the attributes were reviewed and analyzed in order to conduct the research in the 5 dimensions supporting the sustainability of dairy farming businesses through which attributes are the most sensitive and have the most influence on the sustainability of dairy farming businesses among millennial farmers. The study’s results indicate that the sustainability status of millennial livestock businesses in MCP Warnasari is mostly in the less sustainable category.